Preparing for the next pandemic: insights from Aotearoa New Zealand’s Covid-19 response - Nigel P. French; Howard Maxwell; Michael G. Baker; Fiona Callaghan; Kristin Dyet; Jemma L. Geoghegan; David T.S. Hayman; Q. Sue Huang; Amanda Kvalsvig; Euan Russell; Pippa Scott; Te Pora Thompson; et al. (The Lancet Regional Health. Western Pacific)
Summary: In 2020 Aotearoa New Zealand, like many other countries, faced the coronavirus pandemic armed with an influenza-based pandemic plan. The country adapted rapidly to mount a highly strategic and effective elimination response to the SARS-CoV-2 pandemic. However, implementation was hampered by gaps in pandemic preparedness. These gaps undermined effectiveness of the response and exacerbated inequitable impacts of both Covid-19 disease and control measures. Our review examines the Covid-19 response, reflecting on strengths, limitations and implications for pandemic planning. We identify three key areas for improvement: 1) development of a systematised procedure for risk assessment of a new pandemic pathogen; 2) investment in essential capabilities during inter-pandemic periods; and 3) building equity into all stages of the response. We present a typology of potential pathogens and scenarios and describe the evidence assessment process and core capabilities required for countries to respond fluidly, equitably, and effectively to a rapidly emerging pandemic threat.